Inoculation of Potato Pulp with Antibacterial Lactic Acid Bacterium To Improve The Quality of Livestock Feed (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Potato pulp was inoculated either with the antibacterial lactic acid bacteria Lactococcus lactis and L. diolivorans and the inoculated potato pulp was ensiled under anaerobic conditions for 30 d at room temperature in a mini-silo. We have previously reported that L. diolivorans produces antimicrobial peptides with potent antibacterial activity; therefore, the bacterium is expected to increase the fermentation quality of the potato pulp. The quality of the potato pulp silage was evaluated. The moisture content of the potato pulp silage was remained 822 g/kg before and after ensiling. The protein content in the silage increased from an initial concentration of 39 to 57 g/kg and 58 g/kg for L. lactis and L. diolivorans inoculations, respectively. The lactic acid content significantly increased from 2 to 52 g/kg (L. lactis) and 50 g/kg (L. diolivorans) after ensiling, whereas, toxic butyric acid was not detected with either treatment. These results suggest that the inoculation of potato pulp with L. lactis or L. diolivorans increases the quality and nutrition of potato pulp as silage. In particular, L. diolivorans is an efficient inoculant because it produces antibacterial peptides that prevent the increase of saprophyte in silage.